Overview of the iSchool Movement: An Interview with Ronald L. Larsen, iCaucus Chair. (Bulletin of the Association for Information Science & Technology)
EDITOR'S SUMMARY In an interview with the special section guest editors, Ronald L. Larsen, dean of the University of Pittsburgh's School of Information Sciences and chair of the iCaucus, discussed the origins and goals of the iSchool movement, starting in 2005. Larsen explained key differences from traditional information science programs as institutional interest and doctoral programs that reflect intense academic research, paired with core values and expertise to support evolving demands in an increasingly digital world. Criteria for recognition as an iSchool or school of information include expertise or a solid foundation in all forms of information, its use and users and information technology applications. Multidisciplinarity is a strong attraction for many faculty and students. As of early 2016, 65 iSchools existed, over half being outside North America. The iSchools consortium sponsors annual iConferences and has been formalized as a corporate entity dedicated to global recognition, educating information professionals and exploring the effects of information and information technologies.